RIVERSIDE GLAMPING BERARSITEKTUR TROPIS DI TEPI SUNGAI TELAGA WAJA, KARANGASEM : bahasa indonesia - I Wayan Cipta Adi Mahendra; I Wayan Parwata; I Ketut Kasta Arya Wijaya (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Currently, glamping has become a trend for recreation in nature, one type of glamping that is starting to develop is riverside glamping. Riverside Glamping is a tourist accommodation that provides a camping experience while enjoying the natural atmosphere, but can still rest comfortably located on the river bank. One of the areas that has interesting natural potential to be used as a glamping location is in the Karangasem area, precisely along the Telaga Waja river. This glamping design applies a tropical theme using natural materials so that it can respond to the climate in the area. The aim of this glamping design is to accommodate visitors as accommodation which previously was still less than optimal in terms of architecture and comfort. In compiling this journal, data collection methods were used, such as interviews with tourists and tourism object managers around the Telaga Waja river, making direct observations at locations to find the necessary information, and conducting literature studies to obtain information that is still limited in the field. With this glamping design, it is hoped that it can have a positive impact on becoming an icon of a tourist attraction in that location so that it becomes an attraction for tourists so that it can improve the economic sector of the local community